Adjustment of the Framingham index by abdominal aortic calcification scores enables a more accurate prediction of long-term cardiac events in general population aged 40 years and above: evidence from NHANES 2013–2014 - Xiao-Jun Liu; Li Wang; Li-sha Zhang; Li-Fei Cao; Zhao-Fei Wan; Jia-Hong Xue; Yan-Ru He; Xin-Hong Wang; Xiao-Fang Bai (BMC Public Health)
Abstract Background Abdominal aortic calcification (AAC) is considered as a strong predictor of cardiovascular disease (CVD) events. Our study aimed to investigate whether the predicted risk for cardiac death with the Framingham risk score (FRS) could be further improved with the addition of AAC score in general population aged ≥ 40 years. Methods A total of 2971 participants aged ≥ 40 years in the National Health and Nutrition Examination Surveys (NHANES) 2013–2014 were followed up. The Spearman’s rank correlation was performed to explore the correlation between the AAC score and FRS. the Kaplan-Meier method was used to make cumulative cardiac death curve. Predictors of cardiac death was identified by multivariate Cox regression. Additionally, the predictive value of FRS alone and combined with AAC score was estimated by comparing the area under the receiver-operating characteristic (ROC) curve (AUC) and calculating Integrated Discrimination Improvement (IDI). Results During a median of 70.50 months (interquartile range 58.43–82.57 months), 49 (1.649%) experienced cardiac death in the follow-up. The FRS was positively associated with AAC score. Both FRS and AAC score were independent predictors of cardiac death (hazard ratio 1.216; 95%CI 1.135 to 1.302; p < 0.00001; 1.159; 95%CI 1.109 to 1.211; p < 0.00001; respectively). Furthermore, Kaplan-Meier analysis demonstrated increased risk of cardiac death with increasing AAC score (log-rank 54.548, p<0.0001). The predictive value of FRS significantly was improved by adding with AAC score [increase in AUC from 0.734 to 0.780, p < 0.0001; IDI = 0.007, p = 0.013 ]. Conclusions AAC score is positively related with Framingham index, and FBS adjusted by AAC score further improved the prediction risk for cardiac death in general population aged ≥ 40 years.